THE INTERPRETATION OF THE FEMALE IMAGE IN JANE AUSTIN’S NOVEL “PRIDE AND PREJUDICE” - Tukhtaeva Dildora Zokirovna; Abdullayeva Zarinabonu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is about the characters of the novel "Pride and Prejudice" written during the Romanticism period of English literature. You can find a comprehensive analysis of the female figure. A special place in Jane Austen’s work is occupied by one of her six most famous novels," Pride and Prejudice". In the work, the writer depicted not only to the actual social problems of that period, but also revealed the place of women in society in the 18th century. In a word, Jane Austen refers to opposite feelings in the human heart, such as hate and love.